Are the floral morphology and anatomy of Galphimia australis, an atypical neotropical Malpighiaceae, associated to a new pollination syndrome? - Gotelli, Marina María (2022)
The flowers of the species of Malpighiaceae in the Neotropical Region are relatively uniform in their morphology due to their dependence on oil-collecting bees as their main pollinators. However, many species of the genus Galphimia seem to have acquired a different floral syndrome, lacking markedly zygomorphic flowers and developed elaiophores in the calyx. Likewise, these species present anthers with great development, probably in response to the selection of pollinators that collect pollen. Galphimia australis incorporated some of these traits but also retained some residual characteristics typical of species pollinated by oil bees. This leads to many questions on how these flowers ensure their pollination. Inquiring about the reduction or modification of these characteristics allows us to understand how G. australis achieves a different pollination syndrome. In this research, we carry out a detailed morphological and anatomical study of the flowers and pollen grain devolvement of G. australis and floral visitors were observed and captured. Results were analyzed in order to determine how this species changed from the oil-floral syndrome, typical of neotropical Malpighiaceae, to one syndrome with pollen as the main reward.